(untitled) (International Journal of Food and Nutritional Sciences, 2021)
Misinformation has become one of the most resonant phenomena of modern media environments and a major challenge for the continuation of credible journalism. This paper discussed the impact of fake news to legitimate news outlets as it undermines peoples’ trust in journalism. Conducting survey and content analysis along with reviewing literatures, the study explores the impact of fake news on the public perception of journalism. The limitations of the research emphasize the significance of digital media in sharing fake news and provides suggestions for rebuilding the trust in the journalism.